HDAC7 knockout mitigates astrocyte reactivity and neuroinflammation via the IRF3/cGAS/STING signaling pathway - Yue, Rui-zhu; Guo, Xing; Li, Wenqiang; Li, Chaokun; Shan, Linlin (Frontiers in Cellular Neuroscience, 2025)
IntroductionAstrocytes are parenchymal cells widely distributed throughout the brain. Beyond their essential functions in healthy tissue, astrocytes exhibit an evolutionarily conserved response to all forms of brain injury, termed astrocytic reactivity. Nevertheless, conceptual understanding of what astrocytic reactivity encompasses and its functional roles remains incomplete and occasionally contentious. Lipopolysaccharide (LPS) is widely used to induce neuroinflammation. In the current study, Histone deacetylase 7 (HDAC7) has been shown to ameliorate LPS-induced neuroinflammation and mitigate astrocytic reactivity.MethodsWe overexpressed HDAC7 using viral vectors and generated primary astrocytes from Hdac7flox/flox mice to achieve astrocyte-specific HDAC7 knockout. Subsequently, we assessed astrocytic reactivity and detected the expression of the Interferon regulatory factor 3 (IRF3)/cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING) pathway.ResultsHDAC7 has been implicated in inflammatory regulation, but its role in astrocyte reactivity and the underlying mechanisms remain unclear. Here, we demonstrate that HDAC7 deficiency attenuates LPS-induced astrogliosis by suppressing the cGAS/STING signaling axis. LPS stimulation induced robust upregulation of glial fibrillary acidic protein (GFAP), complement component 3 (C3), and pro-inflammatory cytokines (TNF-α, IL-6) in WT astrocytes, which was significantly blunted in HDAC7 knockout astrocytes. Conversely, lentiviral overexpression of HDAC7 in WT astrocytes exacerbated IRF3/cGAS/STING pathway activation, as validated by Western blot analysis showing upregulated cGAS, STING and IRF3 expression. Pharmacological activation of the STING pathway in astrocytes restored pro-inflammatory cytokine expression and reactive marker levels, indicating pathway dependence.DiscussionOur results delineate a novel HDAC7/IRF3/cGAS/STING signaling axis that governs astrocyte reactivity. This discovery provides a crucial cellular neurophysiological mechanism by which astrocytes integrate inflammatory signals and subsequently modulate the central nervous system microenvironment. Targeting HDAC7, therefore, represents a therapeutic strategy to mitigate neuroinflammation by specifically correcting this aberrant cell-physiological state of astrocytes, ultimately preserving neural circuit function.